The Impact of Toy Exploration Activities on Critical Thinking and Speaking Skills in 3-4 Years Old Children - Maureen Audina Sitorus; Ruqoyyah Fitri; Miftakhul Jannah; Andi Kristanto; Utari Dewi; Nina Fajriyah Citra (Studies in Philosophy of Science and Education, 2025)
This study analyzes the impact of toy exploration on the critical thinking and speaking skills of children ages 3-4. Understanding how toy explorations influences these abilities is crucial for parents and educators to support children’s cognitive and communication development effectively. This study processes data using a quasi-experimental approach using JASP. There are 29 participants in this study, and the sample is made up of kids between the ages of 3 and 4. With the experimental group achieving higher ratings of 6.46 and 9 than the control group, the data show that the p-score was less than 0.001. It can be inferred that toy exploration activities have an impact on children's critical thinking and speaking skills between the ages of three and four.